Two new species of Ptecticus Loew, 1855 (Diptera: Stratiomyidae), from bat guano in a Colombian cave - Torres-Toro, Juliana; Pujol-Luz, José Roberto; Wolff, Marta (Zootaxa, 2022)
Genus Ptecticus is widespread distributed in the world, in the Neotropics 51 species have been documented and only four are recorded in Colombia so far. Herein we describe two new species, Ptecticus benecki sp. nov. and Ptecticus pseudospatulatus sp. nov. reared from bat guano in the Colombian Andes. This study contributes to the species richness in the region, ecological records and natural history for the family.